Mutual awareness in collaborative design: An augmented reality integrated telepresence system - Wang, Xiangyu; Love, Peter; Kim, M.; Wang, W. (ELSEVIER, 2014)
Remote collaboration has become increasingly important and common in designers’ working routine. It is critical for geographically distributed designers to accurately perceive and comprehend other remote team members’ intentions and activities with a high level of awareness and presence as if they were working in the same room. More specifically, distributed cognition places emphasis on the social aspects of cognition and asserts that knowledge is distributed by placing memories, facts, or knowledge on objects, individuals, and tools in the environment they work. This paper proposes a new computer-mediated remote collaborative design system, TeleAR, to enhance the distributed cognition among remote designers by integrating Augmented Reality and telepresence technologies. This system can afford a high level externalization of shared resources, which includes gestures, design tools, design elements, and design materials. This paper further investigates how this system may affect designers’ communication and collaboration with focus on distributed cognition and mutual awareness. It also explores the critical communication-related issue addressed in the proposed system, including common ground and social capitals, perspective invariance, trust and spatial faithfulness.